Food and feeding habits of Indian sciaenids - A review - Bhakta, Dibakar; Kumar Das, Sudhir; Das, Basanta Kumar (Indian Journal of Fisheries, 2023)
An attempt was made in the present article to review the food and feeding habits of thefishes of the family Sciaenidae from Indian waters. Members of the Sciaenidae family arecommonly referred to as croakers or drums because of the sound produced by their swimbladders. Sciaenids are distributed in tropical and sub-tropical oceans. They are carnivorous,feeding mainly on crustaceans, small fish, molluscs, annelids and polychaetes and exhibitcannibalism. Sciaenids display differences in food preferences between early stages andadults; the former prefers zooplankton and crustaceans, and the latter mainly smallerteleosts. The feeding intensity was found to be higher in smaller groups compared to maturefish. Considerable temporal variations were recorded in food item occurrence, indicatingan empty stomach during peak breeding and a wide spectrum of food items during otherseasons.Keywords:Croakers, Feeding intensity, Food and feedinghabits, Sciaenids